Student Tutoring, Facilitator and Explaining Models: A Problem Solving Metacognition towards Learning Achievements of Informatics Students - Pratiwi, Merina (Journal of Educational Sciences, 2019)
Metacognition problem solving learning model applied through student tutoring, facilitator, and explaining predicted were able to overcome the low learning achievement of students. The purpose of this research is to know the problem-solving metacognition with learning models of student tutoring, facilitator, and explaining and to find out problem-solving metacognition with learning model of student tutoring, facilitator, and explaining to the students the learning achievements of informatics. This research is descriptive qualitative study uses a quasi- experiment method. Data analysis using independent-test and ANOVA. The results showed that students' problem- solving metacognition is at a low category percentage of35,005%. Problem-solving metacognition of the students with student tutoring, facilitator, and explaining the learning model has no effect against the learningachievements of students of Informatics with F of 0.03 and significant of 0.874.